Defects control for improved electrical properties in(Ba0.8Sr0.2)(Zr0.2Ti0.8)O-3 films by co acceptor doping - Chew, Khian Hooi; Jiang, Y.; Miao, J. (AIP Publishing, 2011)
(Ba0.8Sr0.2)(Zr0.2Ti0.8)O-3 (BSZT) films were grown on La0.5Sr0.5CoO3 buffered (001) SrTiO3 substrates by pulsed laser deposition. Effects of Co doping on electrical properties of the films were investigated to establish material design through defects control. The doping led to a significant improvement in the electrical properties with reduction in leakage current and dielectric loss. In addition, the dielectric tunability and figure of merit were enhanced, implying that Co-doped BSZT films are promising materials for tunable microware applications. Our detail studies suggest that the improved electrical properties of Co-doped BSZT films are closely related to defect concentrations in the films. (C) 2011 American Institute of Physics. [doi:10.1063/1.3666021]